Low Temperature Phase Transitions in Sucrose-Containing Solutions of Some Cryoprotectants - Smolyaninova, Yevgeniya; Bobrova, Olena (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(1):055–058